An Autopsy Study of Atherosclerotic Changes in Coronary Arteries at B.P. Koirala Institute of Health Sciences - Parajuli, Sudhir Raman; Yadav, Bishwonath; Karki, Prahlad; Upadhyaya, Paricha; Jha, Shivendra (Annapurna Journal of Health Sciences, 2023)
Introduction: Atherosclerosis is a giant killer and the incidence of atherosclerosis in coronary arteries is rapidly increasing. The study was designed to assess the atherosclerotic lesions in coronary artery and to correlate the risk factors related to prevalence of atherosclerosis.Methods: Heart from 100 medico legal autopsy cases ranging between ages 15 to 35 years which came to BPKIHS Dharan were taken for this study and processed for coronary arteries using conventional technique. They were then studied,and grading was done based on Modified American Heart Association (AHA) classification of atherosclerosis.Results: Intimal thickening was noted in more than 90% in all three coronary arteries followed by intimal xanthoma whereas intermediate lesion for atherosclerosis was not found. Age, gender, smoking and alcohol in relation to atherosclerosis were found to be of no significance.Conclusion: The study highlights the impact of atherosclerotic lesions in the Eastern region of Nepal. Meticulous postmortem examination along with histopathological study is the best possible way to study atherosclerotic disease in humans and risk factors associated with it.